Hermeneutics in the Perspective of Islamic Education: A Critical Study of the Thoughts of Schleiermacher, Dilthey, and Gadamer - Muhamad Hadli Al Furqon; Alif Aizuddin bin Ahmad Farikh Riaz'uddin (Penerbit Hellow Pustaka, 2025)
Hermeneutics, as an interpretive and epistemological approach, has undergone a significant evolution from its religious roots to its methodological role in the humanities and social sciences. This article critically examines the thought of three key figures in hermeneutics Friedrich Schleiermacher, Wilhelm Dilthey, and Hans Georg Gadamer and their relevance to the development of Islamic education. The study employs a qualitative-philosophical approach using a literature review method, analyzing both primary and secondary works of the three thinkers alongside relevant Islamic education literature. The analysis is conducted through comparative and reflective methods to explore each thinker’s contribution to the foundation of text comprehension methodology, particularly in relation to religious texts. The findings indicate that Schleiermacher emphasized the importance of grammatical and psychological aspects in understanding the author's intent; Dilthey situated hermeneutics within the framework of the humanities, focusing on human historical experience; while Gadamer introduced the concept of the fusion of horizons as the basis for dialogical and historical understanding. Collectively, they offer complementary approaches for shaping a more reflective, contextual, and dialogical practice of Islamic education.The article’s contribution lies in enriching interpretive methodologies within Islamic education, particularly in the teaching of Islamic texts that require a critical and historical approach. These findings affirm that although hermeneutics originates from the Western tradition, it can be contextually adapted within the field of Islamic education to enhance the understanding and relevance of Islamic teachings in contemporary contexts. Therefore, the results of this study are significant for the development of more humanistic and contextual theories and practices in Islamic education.